2018
DOI: 10.5194/acp-18-12141-2018
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and modeling of the multiwavelength optical properties of uncoated flame-generated soot

Abstract: Abstract. Optical properties of flame-generated black carbon (BC) containing soot particles were quantified at multiple wavelengths for particles produced using two different flames: a methane diffusion flame and an ethylene premixed flame. Measurements were made for (i) nascent soot particles, (ii) thermally denuded nascent particles, and (iii) particles that were coated and then thermally denuded, leading to the collapse of the initially lacy, fractal-like morphology. The measured mass absorption coefficient… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 65 publications
(89 reference statements)
6
37
0
Order By: Relevance
“…[rBC] measurements, and are ~35%. The derived MACBC values are very similar to those recently reported by Forestieri et al (2018) for fresh BC particles: MACBC,pure = 11.9 m 2 g -1 at 405 nm and 8.8 m 2 g -1 at 532 nm, with an extrapolated value at 781 nm of 5.7 m 2 g -1 . The value at 532 nm is somewhat higher than that suggested by (7.75 m 2 g -1 at 532 nm).…”
Section: Coating-induced Absorption Enhancementsupporting
confidence: 87%
“…[rBC] measurements, and are ~35%. The derived MACBC values are very similar to those recently reported by Forestieri et al (2018) for fresh BC particles: MACBC,pure = 11.9 m 2 g -1 at 405 nm and 8.8 m 2 g -1 at 532 nm, with an extrapolated value at 781 nm of 5.7 m 2 g -1 . The value at 532 nm is somewhat higher than that suggested by (7.75 m 2 g -1 at 532 nm).…”
Section: Coating-induced Absorption Enhancementsupporting
confidence: 87%
“…We suggest that a reasonable precision-limited uncertainty on the MAC BC,ref values for both campaigns is 10%. It is noteworthy that the derived campaign-specific MAC BC,ref values are in reasonable agreement with laboratory measurements Forestieri et al, 2018) and literature assessments . They are, however, substantially smaller than recently determined from filter-based measurements made across Europe for ambient particles, where the MAC at 637 nm was reported as 10.0 m 2 /g, which would correspond to an MAC at 532 nm of 12 m 2 /g assuming an AAE = 1.…”
Section: 1029/2018jd029501supporting
confidence: 82%
“…Particle composition measurements made using an aerosol mass spectrometer confirmed that the coating material was completely removed and established the relative composition for the mixed coating experiments. The absorption enhancement was determined as the ratio between the coated and uncoated (thermally denuded) particle absorption corrected for losses in the thermodenuder and for the influence of multiply charged particles (42). Further details are available in refs.…”
Section: Methodsmentioning
confidence: 99%